The Influence Of Brand Image, Viral Marketing, And Product Quality On Purchase Intention - Widyarsih, AV Rahajeng; CAHAYA, YOHANES FERRY; Chairul , Al Ghifary (Adpebi International Journal of Multidisciplinary Sciences, 2023)
Purpose – This paper seeks to examine the efficacy of predicting turnover for employees and entrepreneurs from Estonia, Latvia, and Lithuania using attitudes towards benefits, pay satisfaction, pay, gender, and age across a four-year time frame. Methodology/approach – A survey that includes information on brand image, viral marketing and product quality on purchase intention by collecting data from 100 consumers of Kopi Lain Hati Bekasi Jakarta. Findings – It was found that . Brand Image and Product Quality partially had a positive effect and significant effect on Buying Interest on Lain Hati Coffee products, while Viral Marketing partially has a positive and insignificant effect on Buying Interests for Lain Hati Coffee products. Novelty/value – viral marketing is an important factor but not significant to purchase intention